Genomic Alterations in Primary Gastric Adenocarcinomas Correlate with Clinicopathological Characteristics and Survival - Marjan M. Weiss; Ernst J. Kuipers; Cindy Postma; Antoine M. Snijders; Daniel Pinkel; Stefan G. M. Meuwissen; Donna Albertson; Gerrit A. Meijer (Cellular Oncology)
Background & aims: Pathogenesis of gastric cancer is driven by an accumulation of genetic changes that to a large extent occur at the chromosomal level. In order to investigate the patterns of chromosomal aberrations in gastric carcinomas, we performed genome‐wide microarray based comparative genomic hybridisation (microarray CGH). With this recently developed technique chromosomal aberrations can be studied with high resolution and sensitivity. Methods: Array CGH was applied to a series of 35 gastric adenocarcinomas using a genome‐wide scanning array with 2275 BAC and P1 clones spotted in triplicate. Each clone contains at least one STS for linkage to the sequence of the human genome. These arrays provide an average resolution of 1.4 Mb across the genome. DNA copy number changes were correlated with clinicopathological tumour characteristics as well as survival. Results: All thirty‐five cancers showed chromosomal aberrations and 16 of the 35 tumours showed one or more amplifications. The most frequent aberrations are gains of 8q24.2, 8q24.1, 20q13.12, 20q13.2, 7p11.2, 1q32.3, 8p23.1–p23.3, losses of 5q14.1, 18q22.1, 19p13.12–p13.3, 9p21.3–p24.3, 17p13.1–p13.3, 13q31.1, 16q22.1, 21q21.3, and amplifications of 7q21–q22, and 12q14.1–q21.1. These aberrations were correlated to clinicopathological characteristics and survival. Gain of 1q32.3 was significantly correlated with lymph node status (p=0.007). Tumours with loss of 18q22.1, as well as tumours with amplifications were associated with poor survival (p=0.02, both). Conclusions: Microarray CGH has revealed several chromosomal regions that have not been described before in gastric cancer at this frequency and resolution, such as amplification of at 7q21–q22 and 12q14.1–q21.1, as well gains at 1q32.3, 7p11.2, and losses at 13q13.1. Interestingly, gain of 1q32.3 and loss of 18q22.1 are associated with a bad prognosis indicating that these regions could harbour gene(s) that may determine aggressive tumour behaviour and poor clinical outcome.